1999
DOI: 10.1042/0264-6021:3390095
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of specificity for aflatoxin B1-8,9-epoxide in Alpha-class glutathione S-transferases

Abstract: We have used homology modelling, based on the crystal structure of the human glutathione S-transferase (GST) A1-1, to obtain the three-dimensional structures of rat GSTA3 and rat GSTA5 subunits bound to S-aflatoxinyl-glutathione. The resulting models highlight two residues, at positions 208 and 108, that could be important for determining, either directly or indirectly, substrate specificity for aflatoxin-exo-8,9-epoxide among the Alpha-class GSTs. Residues at these positions were mutated in human GSTA1-1 (Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The resistance of adult mice to AFB1 has been suggested to be due to constitutive expression in mouse liver of the A3 subunit of GST (mGSTA3; also known as Yc or Ya 3 ), which exhibits high catalytic activity toward AFB1 (Buetler and Eaton, 1992; Hayes et al, 1992; McDonagh et al 1999). In support of this suggestion are the findings that mGSTA3 confers protection against 8,9-epoxide when transfected into hamster cells (Fields et al, 1999) and that substitution of the five critical mGSTA3 amino acid residues into the rat GSTA3 sequence increases the conjugation activity over 200-fold (van Ness et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The resistance of adult mice to AFB1 has been suggested to be due to constitutive expression in mouse liver of the A3 subunit of GST (mGSTA3; also known as Yc or Ya 3 ), which exhibits high catalytic activity toward AFB1 (Buetler and Eaton, 1992; Hayes et al, 1992; McDonagh et al 1999). In support of this suggestion are the findings that mGSTA3 confers protection against 8,9-epoxide when transfected into hamster cells (Fields et al, 1999) and that substitution of the five critical mGSTA3 amino acid residues into the rat GSTA3 sequence increases the conjugation activity over 200-fold (van Ness et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the activation of AFB 1 can be measured by the formation of a dihydrodiol–Tris adduct [ 50 ]. Quail liver microsomes were used as a positive control as they were reported to be highly active in AFB 1 epoxidation [ 37 , 51 , 52 , 53 ]. The HPLC assays showed that the AFB 1 metabolite produced by quail microsomes had the same retention time as that formed during CYP3A29 reaction with AFB 1 , suggesting that CYP3A29 was capable of oxidizing AFB 1 into AFBO.…”
Section: Discussionmentioning
confidence: 99%
“…That the 2,3-double bond is a critical structural requirement for carcinogenicity and mutagenicity has been pinpointed by structure-activity relationship studies on a variety of structural analogs of AFB 1 [183,184]. Moreover, quantum mechanical calculations have shown that the 2,3-double bond is the most reactive site in the molecule [185,186]. Although attempts to isolate the putative reactive intermediate, AFB 1 -2, 3oxide, have been unsuccessful because of instability, its formation can be deduced from its reaction products with cellular constituents and its hydrolysis products.…”
Section: Metabolism and Mechanism Of Action Of Aflatoxin Bmentioning
confidence: 99%